Carbon capture and utilization in the steel industry: challenges and opportunities for chemical engineering - De Ras, Kevin; Van de Vijver, Ruben; Galvita, Vladimir V; Marin, Guy B; Van Geem, Kevin M (Current opinion in chemical engineering, 2019)
[Display omitted] The availability of green electricity, changes to the Emission Trading Scheme (ETS) system and technological breakthroughs will determine how the steel industry will evolve in the coming decades. The blast furnace (BF) technology will continue to dominate steel production in the coming decade and the only way to substantially reduce the associated CO2 emissions is to combine it with Carbon Capture and Utilization (CCU) and/or Carbon Capture and Storage (CCS). CCU options that do not require a lot of hydrogen and with high added value are logical step stones towards production of bulk chemicals and even fuels such as oxymethylene ethers. BF waste gas recycling and conversion will require a multisectoral approach creating new dependencies between the steel, energy, and chemical sectors. Energy efficient, cheap and CO2 free hydrogen production using green electricity is the ultimate solution to drive this transition. This hydrogen could on the long term also open the door to replace blast furnaces by hydrogen-based steel making. However, today it makes economically more sense to use thermally produced hydrogen by (bio)methane pyrolysis or steam reforming, potentially electrified and intensified, rather than from water electrolysis. Having novel and existing elements from the chemical engineers' toolbox such as artificial intelligence, catalysis and reaction engineering, process intensification principles and multiscale modeling and design, should bring these emerging technologies within reach by the end of the next decade.